Influence of silver nanoparticles on the optical properties of B2O3-CaF2 glass-ceramics containing CaF2 nanocrystals and doped with Pr3+ and Eu3+ - Naranjo, Luz P.; de Araújo, Cid B.; Kassab, Luciana R.P. [UNESP] (My University, 2022)
The influence of silver-nanoparticles (Ag-NPs) on the photoluminescence of rare-earth ions (REI) and CaF2-nanocrystals hosted inside a B2O3-CaF2 glass was investigated. The REI and CaF2-nanocrystals photoluminescence show quenching or enhancement induced by the Ag-NPs.